2021
DOI: 10.20525/ijfbs.v10i3.1352
|View full text |Cite
|
Sign up to set email alerts
|

Equity Investments, Bond Investments and Financial Performance of Collective Investment Schemes in Kenya

Abstract: The collective investment schemes in Kenya have witnessed increased volatility in their earnings, resulting in irregular growth in the industry. This necessitates the need to understand the factors contributing to poor financial returns from collective investment schemes. Hence this study sought to investigate the effect of equity investments and bond investments on Kenyan CIS’s performance. The specific objectives were: To assess the effect of equity investments, bond investments on financial performance of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This is equally supported by Shimave [6] that the investments made by pension schemes positively impact on the market liquidity and capitalization; and recommend that more e-channels should be adopted for wider collection and disbursement purposes. In Kenya, Muema et al, [10] employed the panel regression on 17 collective investment schemes from 2010 -2018; and found that only equity investment have significant impact on the returns of the investment schemes. They suggest that both equity and bond investments should be constantly revised to enable better financial returns.…”
Section: The Intermediation Theory By Gurley and Shawmentioning
confidence: 99%
See 1 more Smart Citation
“…This is equally supported by Shimave [6] that the investments made by pension schemes positively impact on the market liquidity and capitalization; and recommend that more e-channels should be adopted for wider collection and disbursement purposes. In Kenya, Muema et al, [10] employed the panel regression on 17 collective investment schemes from 2010 -2018; and found that only equity investment have significant impact on the returns of the investment schemes. They suggest that both equity and bond investments should be constantly revised to enable better financial returns.…”
Section: The Intermediation Theory By Gurley and Shawmentioning
confidence: 99%
“…Oladeinde [7] evaluated pension reforms in Nigeria's political economy and emphasized key institutional processes and the roles played by international policy advisors. Muema et al, [10] explored on equity and bond investments and its performance on Kenya's investment programs. Shimave [6] studied the effect of the administration of pension funds on stock market growth in Nigeria.…”
Section: Introductionmentioning
confidence: 99%